PENGARUH MODEL PEMBELAJARAN KOOPERATIF STAD TERHADAP HASIL BELAJAR PADA SISWA SMPN 4 SIGI - Agusman, Agusman (Katalogis, 2015)
This research is aimed to know the influence of Cooperative Learning Model of STAD to the learning result of students at SMPN 4 Sigi. This research was Conducted at SMPN 4 Sigi. Using research method that is quasi Experiment Sampling was obtained as propouses sampling from 66 students act divided inter 2 groups, that are Experiment group and control group. Instrument of experiment (average = 83,86 and standart deviation = 5,773) more higt then group control (average = 74,125 and standart deviation = 5,657) and after Condaction ‘t’ test, attained score ‘t’ as 3,0214 whie table ‘t’ at Significancy level 0,05 as 2,00 or t-couret > t-tabel so, it could be unferred that rejectionald Ho and recerved Ha. In this case, the data scored that Cooperative Learning of STAD Can Influence Student Learning result at SMPN 4 Sigi.